2021
DOI: 10.1016/j.renene.2020.07.110
|View full text |Cite
|
Sign up to set email alerts
|

Pressure drops, heat transfer coefficient, costs and power block design for direct storage parabolic trough power plants running molten salts

Abstract: Highlights Molten salts versus thermal oils as heat transfer fluids;  Molten salts show lower pumping electric consumption;  A minimum LCOE reduction of > 6% is expected with HitecXL;  Simpler power block for molten salt technology can be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…This study emphasizes the changes and concerns that are relevant to the replacement of thermic oils with molten salts such as the heat-transmitting coefficient, pressure declining, resistance-freezing solutions, energy bloc design, and price. The results demonstrated pressure declines in the solar domain are shorter running molten salts rather than thermic oil due to elevated temperature operating ranges 12 . Rao et al 26 created a unique thermodynamics prototype to replicate the reaction behaviours of basic and regeneration of CO 2 -TRC-based trough CSP techniques in the presence of diverse fog disturbances.…”
Section: Introductionmentioning
confidence: 93%
“…This study emphasizes the changes and concerns that are relevant to the replacement of thermic oils with molten salts such as the heat-transmitting coefficient, pressure declining, resistance-freezing solutions, energy bloc design, and price. The results demonstrated pressure declines in the solar domain are shorter running molten salts rather than thermic oil due to elevated temperature operating ranges 12 . Rao et al 26 created a unique thermodynamics prototype to replicate the reaction behaviours of basic and regeneration of CO 2 -TRC-based trough CSP techniques in the presence of diverse fog disturbances.…”
Section: Introductionmentioning
confidence: 93%
“…e photothermal technology of the United States, Spain, and other countries is relatively mature, and the investment cost is lower than that in the early stage of industrial development [12]. References [13,14] used the system advisor model (SAM) simulation software to estimate the current and future costs of trough power plants and molten salt tower power plants in the U.S. power market. e prediction results show that the levelized cost of energy (LCOE) of the two power generation technologies will be reduced to 11 cents/kWh, which makes the cost of photothermal power generation competitive compared with the benchmark electricity price of California.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They attained a 29.9% reduction in capital cost by implementing large aperture area PTCs with molten salt as both HTF and storage medium. Lopes et al [ 9 ] showed a 6.3% reduction in LCOE when applying the HitecXL molten salt in a 50 MWe/7.5 h–of–storage power plant. They simulated the plant performance using NREL's System Advisor Model (SAM) software.…”
Section: Introductionmentioning
confidence: 99%